2012
DOI: 10.1007/bf03262460
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals for Blood Pressure Control in Patients with High-Normal or Grade 1 Hypertension

Abstract: Our results show that the addition of Orthosiphon stamineus to the combination of nutraceuticals confers an antihypertensive effect that allows a surprisingly effective 24-hour BP control in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Yin et al reported that approximately 34.5% of patients treated with berberine (500 mg three times daily) experienced transient adverse gastrointestinal effects . Moreover, berberine can lower blood sugar levels and blood pressure and should, therefore, be used with caution in people with diabetes or low blood pressure . Berberine is a potent displacer of bilirubin when tested in vitro using plasma from jaundiced new‐born babies and, therefore, poses a risk of kernicterus .…”
Section: Tolerability and Safetymentioning
confidence: 99%
“…Yin et al reported that approximately 34.5% of patients treated with berberine (500 mg three times daily) experienced transient adverse gastrointestinal effects . Moreover, berberine can lower blood sugar levels and blood pressure and should, therefore, be used with caution in people with diabetes or low blood pressure . Berberine is a potent displacer of bilirubin when tested in vitro using plasma from jaundiced new‐born babies and, therefore, poses a risk of kernicterus .…”
Section: Tolerability and Safetymentioning
confidence: 99%
“…Coenzyme Q10 has consistent and significant antihypertensive effects in patients with essential hypertension . Compared with normotensive patients, essential hypertensive patients have a higher incidence (6‐fold) of coenzyme Q10 deficiency documented by serum levels . Doses of 120 mg/d to 225 mg/d of coenzyme Q10 are necessary to achieve a therapeutic level of 3 μg/mL .…”
Section: Coenzyme Q10 (Ubiquinone)mentioning
confidence: 99%
“…Compared with normotensive patients, essential hypertensive patients have a higher incidence (6‐fold) of coenzyme Q10 deficiency documented by serum levels . Doses of 120 mg/d to 225 mg/d of coenzyme Q10 are necessary to achieve a therapeutic level of 3 μg/mL . This dose is usually 3 mg/kg/d to 5 mg/kg/d of coenzyme Q10.…”
Section: Coenzyme Q10 (Ubiquinone)mentioning
confidence: 99%
See 1 more Smart Citation
“…Another important characteristic of AuNPs is the ability of dissipating heat when absorbing light, being an interest approach for thermal therapy as a trigger to release of encapsulated drugs from thermosensitive hydrogels [9] [17]. Moreover, there are no reports on the use of BS for preparing crosslinked AuNPs hydrogel nanocomposites, despite its relevance in the context of new formulations for biocompatible hydrogels.…”
Section: Introductionmentioning
confidence: 99%